AN OVERVIEW OF TRAINING METHODS THAT PROMOTE THE HIGHEST LIPID OXIDATION DURING AND AFTER A SINGLE EXERCISE SESSION - Barbara Purkart; Boštjan Šimunič; Mitja Gerževič (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2016)
Given that physical activity is the most effective way to increase lipid oxidation, its effects are influenced by several factors. The goal of this review was to identify the most effective methods that facilitate the highest lipid oxidation during and after a single exercise session. For this purpose, the available scientific literature was examined using PubMed, Web of Science, Google Scholar and Cochrane Library databases up to June 2013 with the following keywords: excess post exercise oxygen consumption, exercise fatty acid, energy expenditure exercise and interval training. From the identified 48,583 potentially relevant references, 172 of them met all the required criteria. It was found out that prolonged (> 30 min) moderate intensity (55 − 70 % VO2max) exercise such as walking, jogging or cycling is the most effective way to increase lipid oxidation during and after a single exercise session. Low-volume high-intensity interval exercise is supposed to be as effective as traditional exercise with continuous endurance, with the main effect on lipid oxidation after the session and similar long-term metabolic adaptations. However, more research is still needed to compare the effects of regular resistance exercise with traditional endurance and high-intensity interval exercise. Finally, nutrition is also a significant factor since food rich in fat and low in carbohydrates promotes greater lipid oxidation.